Influence Intellectual Capital And Green Accounting Against Financial Performance with Business Strategy As Moderator - Ni Made Dian Kemala Ratih Palgunadi; Gede Adi Yuniarta; Desak Nyoman Sri Werastuti (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to examine the influence of several variables: (1) intellectual capital and (2) green accounting on financial performance, moderated by the business strategy variable in companies in the basic materials sector listed on the Indonesia Stock Exchange (BEI) from 2020 to 2022. The population in this study consists of 42 companies in the basic materials sector listed on the Indonesia Stock Exchange (BEI) in the main board. Sampling was done using purposive sampling with specific criteria, resulting in 14 samples. The data collection technique used was documentary study by analyzing the financial reports of companies and assessing the PROPER rating results according to the data processing needs. The data were analyzed using SEM PLS version 4.0. The research found that intellectual capital has an impact on financial performance, while green accounting does not have a positive and significant effect on financial performance. Business strategy is able to moderate the relationship between intellectual capital and green accounting on financial performance.